1999
DOI: 10.1200/jco.1999.17.9.2752
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Concurrent Biochemotherapy Modified by Decrescendo Interleukin-2, Granulocyte Colony-Stimulating Factor, and Tamoxifen for Patients With Metastatic Melanoma

Abstract: The data from this study indicate that the modified concurrent biochemotherapy regimen reduces the toxicity of concurrent biochemotherapy with no apparent decrease in response rate in patients with poor prognosis metastatic melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
2
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 22 publications
3
64
2
1
Order By: Relevance
“…In this study, brain metastasis did not develop as the first or concurrent site of progressive disease in patients with either responsive disease (n ¼ 23) or with stable disease (n ¼ 13). Two prior published reports have indicated brain metastasis as a first site of progressive disease in four out of nine patients with a complete remission (Legha et al, 1998;O'Day et al, 1999). Moreover, in a retrospective case-controlled study of responders to DTIC or TMZ, it was found that responders to TMZ developed significantly less CNS relapses than responders to DTIC (Paul et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In this study, brain metastasis did not develop as the first or concurrent site of progressive disease in patients with either responsive disease (n ¼ 23) or with stable disease (n ¼ 13). Two prior published reports have indicated brain metastasis as a first site of progressive disease in four out of nine patients with a complete remission (Legha et al, 1998;O'Day et al, 1999). Moreover, in a retrospective case-controlled study of responders to DTIC or TMZ, it was found that responders to TMZ developed significantly less CNS relapses than responders to DTIC (Paul et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies of chemo-immunotherapy in metastatic melanoma, no response was observed in brain metastases despite objective tumour regression at extracranial sites (Legha et al, 1998;O'Day et al, 1999).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…There are a variety of treatments available for patients with poor prognosis such as chemotherapy, active-specific immunotherapy (vaccine), cytokine therapy, and biochemotherapy that have shown some promising clinical responses. [3][4][5][6] In addition, many new treatments are being developed that need to be validated in randomized clinical trials. To date, although these therapeutic interventions may prolong survival, there is basically no cure rate for advanced disease.…”
mentioning
confidence: 99%